PELAKSANAAN PERLINDUNGAN HUKUM TERHADAP ANAK DIBAWAH UMUR YANG BEKERJA SEBAGAI PENJUAL KORAN DI KOTA SAMARINDA DITINJAU DARI UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERUBAHAN ATAS UNDANG-UNDANG N0M0R 23 TAHUN 2002 TENTANG PERLINDUNGAN ANAK - Yuni Yuni (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
ABSTRACTThe phenomenon of underage labor that occurs in the city of Samarinda today, such as being a very ordinary sight. Increasing the number of child laborers in samarinda city, is a problem that is quite precarious to immediately pursue a solution both by the Government and related parties.The method used in this writing is empirical juridical research method, which is a method of legal research that uses the rules in legislation and seeks data or information directly in the form of interviews with sources.The results stated that there are a variety of factors that cause minors to work as newspaper sellers in Samarinda city umunya family factors, then economic factors, as well as factors of mental damage of children. Many efforts have been made by the Government of Samarinda City Social Service which aims to reduce child labor by means of street control, coaching and socialization to child workers.The implementation of legal protection and constraints on minors who work as newspaper sellers in Samarinda City is in this case the Social Service of Samarinda City has made every effort to reduce the number of minor workers who work as newspaper sellers but until now have not received maximum results. This is with indicators of the number of minors in various places in the corner of Samarinda city need evaluation in handling and rare more intensive in order to get maximum results Keywords: Child Labor, Child Protection, Child Protection